System Information Audit with COBIT 4.1 and Balanced Scorecard Framework (Case Study: PT. Boga Dimsum Indonesia) - Handy Ghasali; Kevin Christianto (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
The advancement of information technology has led people more easily to connect with each other and provide value added in the form of efficiency and effectiveness that produce something for meeting purposes, record customer complaints, answer customer questions, convey information to customers, provide warranty, and seek profit by this utilization. The reason for the audit of SI in this study is PT. Boga Dimsum Indonesia where the company needs an audit on the inventory and accounting intregrated system because there is an error in the purchase application. In this research, the method used is qualitative research method that is research about descriptive research and tend to use analysis. The purpose of the audit is to know whether the information technology governance applied by PT. Boga Dimsum Indonesia has gone well. The research consists of 4 stages: planning, Field Work, Reporting, Follow Up. Based on the results of this study can be concluded that the IT functions contained in PT. Boga Dimsum Indonesia is not yet optimal.